Effects of high-fiber diets enriched with carbohydrate, protein, or unsaturated fat on circulating short chain fatty acids: results from the OmniHeart randomized trial. Issue 3 (11th January 2020) - Mueller, Noel T; Zhang, Mingyu; Juraschek, Stephen P; Miller, Edgar R; Appel, Lawrence J
ABSTRACT: Background: Short chain fatty acids (SCFAs; e.g., acetate, propionate, and butyrate) are produced by microbial fermentation of fiber in the colon. Evidence is lacking on how high-fiber diets that differ in macronutrient composition affect circulating SCFAs. Objectives: We aimed to compare the effects of 3 high-fiber isocaloric diets differing in %kcal of carbohydrate, protein, or unsaturated fat on circulating SCFAs. Based on previous literature, we hypothesized that serum acetate, the main SCFA in circulation, increases on all high-fiber diets, but differently by macronutrient composition of the diet. Methods: OmniHeart is a randomized crossover trial of 164 men and women (≥30 y old); 163 participants with SCFA data were included in this analysis. We provided participants 3 isocaloric high-fiber (∼30 g/2100 kcal) diets, each for 6 wk, in random order: a carbohydrate-rich (Carb) diet, a protein-rich (Prot) diet (protein predominantly from plant sources), and an unsaturated fat–rich (Unsat) diet. We used LC-MS to quantify SCFA concentrations in fasting serum, collected at baseline and the end of each diet period. We fitted linear regression models with generalized estimating equations to examine change in ln-transformed SCFAs from baseline to the end of each diet; differences between diets; and associations of changes in SCFAs with cardiometabolic parameters. Results: From baseline, serum acetate concentrations were increased by the Prot (β: 0.24; 95% CI: 0.12, 0.35), Unsat (β: 0.21; 95% CI: 0.10, 0.33), and Carb (β: 0.12; 95% CI: 0.01, 0.24) diets; between diets, only Prot compared with Carb was significant ( P = 0.02). Propionate was decreased by the Carb (β: −0.10; 95% CI: −0.16, −0.03) and Unsat (β: −0.10; 95% CI: −0.16, −0.04) diets, not the Prot diet; between diet comparisons of Carb vs. Prot ( P = 0.006) and Unsat vs. Prot ( P = 0.002) were significant. The Prot diet increased butyrate (β: 0.05; 95% CI: 0.00, 0.09) compared with baseline, but not compared with the other diets. Increases in acetate were associated with decreases in insulin and glucose; increases in propionate with increases in leptin, LDL cholesterol, and blood pressure; and increases in butyrate with increases in insulin and glucose, and decreases in HDL cholesterol and ghrelin ( P s < 0.05). Conclusions: Macronutrient composition of high-fiber diets affects circulating SCFAs, which are associated with measures of appetite and cardiometabolic health. This trial was registered at clinicaltrials.gov as NCT00051350.